Conflicts of interest and the future of medicine : the United States, France, and Japan - Rodwin, Marc A. (New York ; Oxford : Oxford University Press, 2011)
This book examines the development of conflicts of interest in the healthcare systems of the US, France, and Japan. It shows that national differences in the organization of medical practice and the interplay of organized medicine, the market, and the state give rise to variations in the type and prevalence of such conflicts.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Medical economics -- United States; Medical economics -- Japan; Medical economics -- France; Conflict of interests -- United States; Conflict of interests -- Japan; Conflict of interests -- France